Engineers military objects in the Development of military-historical museum - Mashtalir, V.V. (Питання історії науки і техніки, 2014)
This research investigates the problem of adapting engineering military installations to the conditions of their use for certain utilitarian function in modern society. An analysis and shows the importance and influence of functioning of the engineering military installations of the museum demonstration at the military historical museums.